New proof of Nagnibida's theorem - Mubariz T. Karaev (Journal of Function Spaces and Applications)
Using the Duhamel product for holomorphic functions we give a new proof of Nagnibida’s theorem on unicellularity of integration operator Jα,(Jαf)(z)=∫αzf(t)dt, acting in the space Hoℓ(Ω).